(untitled) (Patan Pragya, 2025)
This paper thoroughly evaluates the key obstacles confronting Tribhuvan University in particular and other higher educational institutions of Nepal in general. Employing a secondary-analysis method involving governmental reports, multilateral development documents, scholarly writings and research papers termed as peer-reviewed literature, it combines evidence on access and equity, governance and regulation, quality assurance and academic standards, funding and resource limitations, faculty capability and research productivity, infrastructure and digital disparities, and relevance to labor market requirements in general and challenges faced by Tribhuvan University in particular. The paper concludes with specific policy and institutional suggestions for enhancing higher education—highlighting cohesive governance, sustainable funding, quality control, research capacity enhancement, and strategies for inclusive access. The paper accords some indispensable recommendations for policy makers, higher education institutions (HEIs), Tribhuvan University and global collaborators in academic domain. This paper has employed critical analysis as a research tool to undertake the research on the pivotal topic.